PENGARUH CURIOSITY TERHADAP HASIL BELAJAR FISIKA KELAS XII IPA DI SMA NEGERI 1 CARIU KABUPATEN BOGOR - RINA SETYAWATI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to determine whether curiosity has an influence on the learning outcomes of physics in class XII IPA at SMA Negeri 1 Cariu, Bogor Regency. This type of research used is quantitative research using regression analysis test. The sampling technique used simple random sampling technique. The data collection technique is in the form of a questionnaire instrument for students' curiosity data and a test instrument for collecting physics learning outcomes. Measurement of learning outcomes in the cognitive domain uses formative tests in the form of description questions on magnetic field material. The curiosity measurement questionnaire instrument uses a Likert scale with alternative answers always (SL), often (SR), sometimes (KD), and never (TP). For the scoring of favorable statements, that is always given a score of 4, often given a score of 3, sometimes given a score of 2, and never given a score of 1. Meanwhile, scoring of unfavorable statements is always given a score of 1, often given a score of 2, sometimes given a score a score of 3, and never given a score of 4. Based on the results of the calculation of the regression analysis test, it can be concluded that there is an influence of curiosity on the results of learning physics in class XII IPA at SMA Negeri 1 Cariu, Bogor Regency. This is indicated by the acquisition of a significance value of 0.000 <0.05 and tcount 5.613 > ttable 1.999. The regression equation Y = 43.306 + 0.331x that for every addition of curiosity by 1 unit, the value of physics learning outcomes for class XII IPA increases by 0.331. The regression coefficient is positive so that it can be said that the direction of the influence of the curiosity variable on physics learning outcomes is positive. The magnitude of the coefficient of determination (R square) is 0.337 which means that the effect of curiosity on physics learning outcomes is 33.70% while the remaining 66.30% is influenced by other factors not examined. ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah curiosity memiliki pengaruh terhadap hasil belajar fisika kelas XII IPA di SMA Negeri 1 Cariu Kabupaten Bogor. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan menggunakan uji analisis regresi. Teknik pengambilan sampel menggunakan teknik simple random sampling. Teknik pengumpulan data berupa instrumen angket untuk data curiosity peserta didik dan instrumen tes untuk pengumpulan hasil belajar fisika. Pengukuran hasil belajar pada ranah kognitif ini menggunakan tes formatif berupa soal uraian pada materi medan magnetik. Instrumen angket pengukuran curiosity menggunakan skala likert dengan alternatif jawaban selalu (SL), sering (SR), kadang-kadang (KD), dan tidak pernah (TP). Untuk penyekoran pernyataan favorable, yaitu selalu diberi skor 4, sering diberi skor 3, kadang-kadang diberi skor 2, dan tidak pernah diberi skor 1. Sedangkan untuk penyekoran pernyataan unfavorable yaitu selalu diberi skor 1, sering diberi skor 2, kadang-kadang diberi skor 3, dan tidak pernah diberi skor 4. Berdasarkan hasil perhitungan uji analisis regresi, maka dapat disimpulkan bahwa diperoleh bahwa terdapat pengaruh curiosity terhadap hasil belajar fisika kelas XII IPA di SMA Negeri 1 Cariu Kabupaten Bogor. Hal ini ditunjukkan dengan perolehan nilai signifikansi 0,000 < 0,05 dan thitung 5,613 > ttabel 1,999. Persamaan regresi Y = 43,306 + 0,331x bahwa setiap penambahan curiosity sebesar 1 satuan, maka nilai hasil belajar fisika kelas XII IPA bertambah sebesar 0,331. Koefisien regresi tersebut bernilai positif sehingga dapat dikatakan bahwa arah pengaruh variabel curiosity terhadap hasil belajar fisika adalah positif. Besarnya koefisien determinasi (R square) sebesar 0,337 yang berarti pengaruh curiosity terhadap hasil belajar fisika sebesar 33,70% sedangkan sisanya 66,30% dipengaruhi oleh faktor-faktor lain yang tidak diteliti.